SPORTS, PHYSICAL ACTIVITY AND PELVIC FLOOR MUSCLE DISORDERS - Iuliana BOROS-BALINT; Dumitru Rareş CIOCOI-POP; Agnes SIMON-UGRON; Anca Lucia VĂDAN (Cluj University Press, 2019)
Introduction: Physical activity is essential to leading a healthy lifestyle; however, in some cases (when not adequate to one's individual needs, both quantitatively and qualitatively), it might lead to unforeseen outcomes. One such consequence is pelvic floor muscle dysfunction, nowadays a major public health problem, mainly because of its impact on the quality of life of the general population and the associated high health costs, respectively. Material and Methods: The articles used for the study were available via online databases. Our research is based solely on studies written in English, out of which 65 represent the main frame of this paper. Results: Participating in high-intensity physical activities (competitive sports, challenging manual labour) can increase the load on pelvic floor muscles. What is more, overloading the pelvic floor muscles might lead to disorders such as incontinence or pelvic organs prolapse. Some studies showed a 41% prevalence of urinary incontinence in elite athletes. This prompted us to review the circumstances leading to the pelvic floor disorders, more specifically, the relationship between physical activity and pelvic floor muscle dysfunctions. The analysis was based on the available published literature. Physical activity (PA) refers not only to recreational and regular physical training, but also to household tasks and other work-related and transport-related undertakings. Women engaged in hard manual labour can be 9.6 times more likely to have stage 2-4 grade uterine prolapse. Conclusions: Women suffering from urinary stress incontinence should be encouraged to participate in regular leisure and fitness activities and women engaged in vigorous physical activity have to be forewarned. Specific perinea muscle reinforcement may be needed in order to maximize the pelvic floor muscle strength. REZUMAT. Sportul, activitatea fizică și disfuncțiile musculaturii planșeului pelvian. Introducere: Activitatea fizică este esențială pentru a avea un stil de viață sănătos; cu toate acestea, atunci când nu este adaptată nevoilor individuale, atât din punct de vedere calitativ, cât și din punct de vedere cantitativ, ea poate avea urmări nedorite. Una dintre aceste consecințe nedorite este afectarea musculaturii planșeului pelvian, considerată în prezent o problemă majoră de sănătate publică, datorită atât impactului negativ asupra calității vieții, cât și costurilor mari pe care le generează. Material și Metode: Articolele introduse în acest studiu au fost selectate din bazele de date disponibile online. Au fost căutate doar articole în limba engleză, fiind selectate 65 dintre acestea. Rezultate: Practicarea activităților fizice de mare intensitate (sport, muncă fizică solicitantă) poate crește solicitarea musculaturii planșeului pelvian. Suprasolicitarea musculaturii planșeului pelvian poate duce la incontinență urinară sau la prolapsul organelor pelviene. Unele studii indică o prevalență de 41% a incontinenței urinare în rândul sportivelor de performanță. Drept urmare, am decis să investigăm condițiile în care apare afectarea musculaturii planșeului pelvian, precum și legătura dintre activitatea fizică și afectarea musculaturii planșeului pelvian, bazându-ne pe literatura de specialitate disponibilă online. Prin activitate fizică se înțelege nu doar activitatea fizică practicată în mod regulat sau recreațional, ci și munca fizică sau căratul. Femeile care prestează muncă fizică grea au un risc de 9.6 ori mai mare de a prezenta prolaps uterin de gradul 2-4. Concluzii: Femeile care suferă de incontinență urinară de efort trebuie încurajate să practice în mod regulat activități fizice recreaționale, iar femeile care practică activități fizice de mare intensitate trebuie să fie prevenita asupra riscurilor. Exercițiile specifice pentru planșeul pelvian pot fi utile pentru a crește rezistența musculaturii de la acest nivel. Cuvinte cheie: activitate fizică, sport, muncă fizică, disfuncțiile musculaturii planșeului pelvian.